Boolean Algebra differs from both general mathematical algebra and binary number system. In Boolean Algebra, A+A =A and A.A = A, because the variable A has only logical value. It doesn’t have any numerical significance. In ordinary mathematical algebra, A+A = 2A and A.A = A2, because the variable A has some numerical value here. Also, in Binary Number System 1+1 = 10, and in general mathematical algebra 1+1 = 2 but in Boolean Algebra 1+1 = 1 itself. Unlike ordinary algebra and Binary Number systems here is subtraction or division in Boolean Algebra. We only use AOI (AND, OR and NOT/INVERT) logic operations to perform calculations in Boolean Algebra.

Axioms in Boolean Algebra: There are some set of logical expressions which we accept as true and upon which we can build a set of useful theorems. This set of logical expressions are known as Axioms or postulates of Boolean Algebra. An axiom is actually nothing more than definition of three basic logic operations (AND, OR and NOT). Each axiom can be interpreted as the outcome of an operation performed by a logic gate.

- Axiom 1: 0.0 = 0 Axiom 6: 0+1 = 1
- Axiom 2: 0.1 = 0 Axiom 7: 1+0 = 1
- Axiom 3: 1.0 = 0 Axiom 8: 1+1 = 1
- Axiom 4: 1.1 = 1 Axiom 9: = 1
- Axiom 5: 0+0 = 0 Axiom 10: = 0

Read also: Need algebra homework help? Look no further! EduBirdie is at your service!

Based on these axioms we can conclude many laws of Boolean Algebra which are listed below.

1.) Commutative Laws: (a) A+B =B+A and (b) A.B = B.A

2.) Associative Laws: (a) (A+B) + C = A+(B+C)

(b) (A.B). C = A. (B.C)

3.) AND Laws: (a) A.0 = 0 (b) A.1 = A

(c) A.A = A (d) A. = 0

4.) OR Laws: (a) A+0 = A (b) A+1 = 1

(c) A+A = A (d) A+ = 0

5.) Complementation Laws: (a) If A = 0 then = 1

(b) If A = 1 then = 0

(c) = A

6.) Distributive Laws: (a) A(B+C) = AB + AC

(b) A + BC = (A+B). (A+C)

7.) Idempotence Law: (a) A.A =A

If A=1, then A.A = 1.1 =1 = A and if A=0, then A.A = 0.0 = 0 = A

(b) A+A = A

If A=1, then A+A = 1+1 =1 = A and if A=0, then A+A = 0+0 = 0 = A

8.) Absorption Law: (a) A + A.B = A

(b) A.(A+B) = A

9.) De-Morgan’s Law: (a) = .

(b) = +

10.) Consensus Theorem: (a) AB + C + BC = AB + C

Proof: LHS = AB + C + BC

= AB + C + BC (A+)

= AB + C + ABC + BC

= AB (1+C) + C (1+C)

= AB + C = RHS

(b) (A+B) ( + C) (B+C) = (A+B) ( + C)

Proof: LHS = (A+B) ( + C) (B+C)

= (A + AC + B + BC) (B+C)

= (AC + B + BC) (B+C)

= ABC + ACC + BB + BC + BCB + BCC

= ABC + AC + B + BC + BC + BC

= ABC + AC + B + BC + BC

= AC(B+1) + B (1+C) + BC

= AC + B + BC …………… (Equation 1)

RHS = (A+B) ( + C)

= A + AC + B + BC

= AC + B + BC ……………… (Equation 2)

Since, Equation 1 = Equation 2, Hence Consensus Theorem is verified.